Comparing endoscopic microdebrider assisted adenoidectomy with curettage procedure - Ravishakar, C.; Killera, Shambulinga (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Adenoid is a mass of lymphatic tissue situated posterior to the nasal cavity, in the roof of the nasopharynx, forming a part of the Waldeyer's ring, was initially described in 1868 by Meyer. Adenoidectomy is one of the commonest operations done on children. It is done alone or along with tonsillectomy or with ventilation tube insertion for otitis media with effusion. Objective of the study was to compare the results of endoscopic microdebrider assisted adenoidectomy with that of conventional curettage adenoidectomy. Methods: A prospective randomized study of 60 patients with clinical features of adenoid hypertrophy. These patients were randomly divided into two groups, 30 each using the table of random numbers. Group I, underwent endoscopic microdebrider assisted adenoidectomy and group II underwent adenoidectomy by curettage. All the patients were followed up for a period of 3 months. Parameters such as operating time, blood loss, intra-operative/post-operative complications and residual adenoid tissue were assessed. Results: In this study mean age of patients in group I (EAA) was 9±0.50 years (range 6–15 years) and group II (CA) was 9.86 ± 2.31 years (range 6-15 years). The mean operating time was 20.79 minutes for the group I (range: 12 to 35 minutes) and 14.42 minutes for group II (range: 10 to 22 minutes, p=0.001). Blood loss was around 31.06 ml (range: 21 to 46 ml) in group I and 22.26 ml (range: 10 to 60 ml) in group II. Adenoidectomy by curette group showed more residual nasopharyngeal adenoid tissue (43.33%) than by endoscopic microdebrider assisted adenoidectomy (20%). Conclusions: Endoscopic microdebrider assisted adenoidectomy is a safe and more effective compared to curettage method, with very minimal chances of injury to the surrounding structures during the procedure.